2020
DOI: 10.3389/fimmu.2020.00249
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced Tryptophan Breakdown is Related With Anemia, Fatigue, and Depression in Cancer

Abstract: Many patients with cancer suffer from anemia, depression, and an impaired quality of life (QoL). These patients often also show decreased plasma tryptophan levels and increased kynurenine concentrations in parallel with elevated concentrations of Th1 type immune activation marker neopterin. In the course of anti-tumor immune response, the pro-inflammatory cytokine interferon gamma (IFN-γ) induces both, the enzyme indoleamine 2,3-dioxygenase (IDO) to degrade tryptophan and the enzyme GTP-cyclohydrolase I to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 289 publications
(238 reference statements)
5
110
0
1
Order By: Relevance
“…Tryptophan metabolism is triggered by inflammation and/or degeneration in diabetes, causing increased Kyn metabolites 47 . Oxenkurg 25,26 has reported that, a high level of Kyn/Trp is associated with altered Trp levels in hemodialysis patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan metabolism is triggered by inflammation and/or degeneration in diabetes, causing increased Kyn metabolites 47 . Oxenkurg 25,26 has reported that, a high level of Kyn/Trp is associated with altered Trp levels in hemodialysis patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the potential new targets, the environment of inflammation has received considerable attention and become an immunotherapy challenge for re-inducing an antitumoral response. [7][8][9] TNF-α and ILs are pro-inflammatory cytokines produced by lymphocytes and macrophages, which can induce apoptosis of tumor cells and are associated with the progression of several types of tumors, including OS. 10,11 In addition, TNF-α and ILs are transcriptionally controlled by NF-kB and C3 signaling 12,13 ; therefore, searching the upstream key factors to regulate the inflammatory response may be a vital step in the treatment of osteosarcoma.…”
mentioning
confidence: 99%
“…Incidence of PLC is closely related to choric virus infection and/or cirrhosis, which present tumor cells existing in an in ammatory microenvironment [50][51][52]. Interleukin-17 (IL-17) family produced by CD4+ T helper (Th) cells plays a vital role in orchestrating host immune responses [53].…”
Section: Discussionmentioning
confidence: 99%